Analisis Keunggulan Usaha Online Pada Mahasiswa - Nur Alfiana Kholizah; Intan Nuraini; Lucky Tirta Nurarfiansyah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Students have high potential and interest in entrepreneurship, and have innovative, confident, open to new things, dare to take risks, like to plan, and never give up. In addition, innovation of student business products is a major strength in shaping the ability to develop a business. Capital and creativity are considered as obstacles in starting a business. Students also see great opportunities in online business. Therefore, students have great potential and interest in entrepreneurship, including in online business. This study aims to determine the analysis of the advantages of online businesses in college students. Which is where the analysis of the advantages of online businesses in college students shows that many students choose online businesses because of their similarities, relatively low costs, and access to a wider market. They can better manage their study and business time, and gain entrepreneurial experience. However, challenges such as fierce competition and lack of business experience are also worth noting. Therefore, students need to carefully consider the quality of the goods being sold so that buyers are not disappointed. With the development of globalization and the rapid development of the times, we as students are able to do business or look for opportunities to increase pocket money or increase our own income by doing business online.